Analisis Komparasi Pengaruh CKPN dan Profitabilitas Terhadap Permodalan Bank yang Diukur Melalui Rasio Car Sebelum dan Sesudah Adaptasi PSAK 71 (Studi Kasus pada Bank Umum Buku 2 Yang Teregistrasi di OJK) - Farhan Zaki; Sudrajat Sudrajat (Jurnal Mutiara Ilmu Akuntansi, 2024)
Competition between commercial banks is increasingly rapid and complex, causing changes in regulations that are binding on commercial banks. One of the regulatory changes is the application of PSAK 71 which replaces PSAK 55 concerning Financial Instruments. A previous study conducted by Suroso in 2017 simulated the impact of implementing PSAK 71 on bank performance as measured by the capital ratio, namely the Capital Adequacy Ratio. The results of this study stated that there was a decrease in the CAR ratio due to an increase in CKPN which was caused by a change in the CKPN calculation method. This research will measure the comparative influence of CKPN, ROA, and Size as control variables on the CAR ratio at BUKU "2" Commercial Banks. As well as analyzing whether there is a difference in the CAR of commercial banks between before and after the implementation of PSAK 71. The results of the study show that the CKPN, ROA, and Size of the CAR of banks when implementing PSAK 55 has a value of 19.4%. This result is better than the implementation of PSAK 71 which amounted to 14.3%. Apart from that, there is a significant difference in the CAR ratio between before and after the implementation of PSAK 71. This difference is due to the high CKPN and the Covid-19 pandemic forcing banks to hold back credit distribution. So the risk of the bank's RWA has decreased, causing the bank's CAR to increase even though the CKPN has increased, and the bank's ROA has decreased.